Poromechanical effect in the lithium–sulfur battery cathode. (December 2016) - Barai, Pallab; Mistry, Aashutosh; Mukherjee, Partha P.
Abstract: In lithium–sulfur (Li–S) batteries, during discharge, solid sulfur (S 8 ( s ) ) gets dissolved and undergoes successive reduction and finally precipitates as lithium sulfide (Li 2 S) in a typical carbon-based, porous cathode. Deposition of Li 2 S leads to 80% volume expansion compared to solid S 8 ( s ) . During the dissolution–precipitation process, the total volume change of the electrolyte in the pore space can be attributed to two factors: (a) precipitation/dissolution of the solid sulfur phase; and (b) the cathode microstructure shrinks or swells to accommodate the changes in the pore volume resulting from the electrolyte induced hydrostatic pressure. Current lithium–sulfur performance models neglect this contribution. In this work, a computational methodology has been developed to quantify the impact of precipitation induced volume change, pore morphology and confinement attributes in a Li–S cathode. Impact of volume expansion on cell voltage has also been analyzed using a performance model. It is found that the poromechanical interaction significantly affects the second voltage plateau. Cathode microstructures with relatively smaller pores tend to experience less volume expansion, for the same operating conditions. It has been found that non-uniform precipitation may lead to significant pore confinement, which has the potential to cause microcrack formation in the pore walls of a typical carbon-based cathode microstructure.